Evaluación de la hormona coriónica equina para disminuir la muerte embrionaria en vacas - Álava Cobeña, Jorge Eduardo (2013)
ABSTRACT This research was conducted in the town of San Vicente - province of Manabí in the company "Agricultural El Naranjo SA” in the Ranch El Napo, which evaluated the effect of equine chorionic hormone (eCG) to reduce embryonic death in cows. 40 animals were used, divided into two groups, 20 treated with eCG and 20 as control group without eCG. A protocol with new intravaginal devices, and estradiol benzoate hormones, prostaglandin and equine chorionic hormones were at fixed-time inseminated (AFTI). Statistical evaluation was performed using logistic regression and the presence of pregnancy were compared with the Tukey test, finding significant differences (p <0.01%) and (p> 0.05%) to be held the first gynecological check within thirty days, while in the second checkup to sixty days, there were no differences in therefore the application of the eCG did not reduce embryonic death presented the same rate in both groups, however using eCG the progesterone levels vary from 11.60 ng/ml as the highest and the lowest is 6.20 ng/ml in pregnant cows. As for the economic analysis, the research showed no profitability by applying eCG, because for every dollar invested was lost 0.31 cents.